On efficient testing of capacity constraints in pickup-and-delivery problems with trailers - Michael Drexl (4OR, 2020)
Efficient feasibility tests are important in many heuristics for routing problems. This paper considers several variants of pickup-and-delivery problems with trailers. Its contribution consists in the description of constant-time procedures for testing observance of capacity constraints when inserting tasks into routes. It is demonstrated that the presence of vehicles with detachable trailers makes capacity feasibility tests considerably more involved.
Keywords: B06: Transportation; logistics; 650; Routing; Pickup-and-delivery; Trailers; Constant-time feasibility test